POLISH ENTREPRENEURS EXPECTATIONS AND FEARS IN THE FACE OF THE INTEGRATION WITH EUROPEAN UNION - Kurek, Iwona; Sawicka, Janina (Acta Scientiarum Polonorum. Oeconomia, 2003)
The aim of the paper is to present results of the survey that was conducted among 200 women running small firms in rural areas in 2003. Particularly the opinions, fears and hopes, connected with the European integration have been presented. On the grounds of own researches as well as the available literature, the authors has presented the analysis of opportunities and threatens (SWOT) of Polish small and medium-sized enterprises (SME) sector in relation to the integration.